Henan - the model: from hegemonism to fragmentism ; portrait of the political culture of China's most populated province - Heberer, Thomas; Jakobi, Sabine (2000)
Abstract: "Henan is China's most populous province. It has long played a strategic role in Chinese history and in more recent decades has played a prominent part in the country's politics. In this paper we explore aspects of the history and political culture of Henan, particularly the collective memory or consciousness of its people, and trends in its recent political history. We focus in particular on specific cultural features and local patterns of socio-economic development, both to highlight important features of provincial life and also to provide an interpretive strategy for approaching recent developments in the province. In identifying specific cultural features, we focus heavily on the egalitarian heritage of the province - in some cases bordering on communitarianism - and how this heritage relates to a deeply-rooted sense that Henan has lost its central role in China's national life. These two patterns converge, today, to produce a phenomenon of 'modelism' in Henan - a tendency to